Study of the Effect of Bone Marrow Aspirate on Denervated Muscle According to CT and MRI Studies - Strafun, S.S.; Lysak, A.S.; Tretiakov, R.A. (TERRA ORTHOPAEDICA, 2021)
Summary. Relevance. Peripheral nerve injury leads to severe limb dysfunction due to denervation, hypotrophy, and skeletal muscle degeneration. Non-invasive visualization methods of these changes are sonography, CT, and MRI. Objective: to study in the experiment the effect of bone marrow aspirate on the course of denervation and reinnervation processes in skeletal muscles using CT and MRI. Materials and Methods. The experiment was performed on 36 rabbits, which are divided into four groups: a group of pseudooperated animals, group 1 (neurotomy and sciatic nerve suture), group 2 (on-time injection of bone marrow aspirate), and group 3 (delayed injection of bone marrow aspirate). CT was performed on a Philips Brilliance 16; MRI was performed on a Philips Achieva 1.5 Tesla. Results. The study results of pseudooperated animals did not differ from the norm. There was a significant (p<0.05) difference in X-ray density between the target muscles of the operated and non-operated limb. The overall larger cross-sectional area of the target muscles was noted in group 2 (median 1.15 cm2), slightly smaller in group 1 (1.1 cm2), and the smallest in group 3 (1.0 cm2). The total X-ray density of the target muscles also differed, with the highest in group 1 (median 69.21 HU), less in group 2 (67.66 HU), and the lowest in group 3 (66.82 HU). We found a significant (p<0.05) difference between the MR signal strength of the target muscles in the T1 mode between groups 1 and 2. Conclusions. Bone marrow aspirate injection into the target muscles helps reducing muscle swelling. The intensity of the MR signal expression in the T1 mode in the group where the bone marrow aspirate injection was not performed was significantly (p<0.05) greater than in the groups with aspirate injection. The time of bone marrow aspirate injection to the target muscles did not significantly affect the parameters of CT and MRI signal.